"Hangd for the True Faith": Embodied Devotion in Early Modern English Carmelite Cloisters. (18th November 2020) - Walker, Claire
Abstract : The annals of the English Carmelites of Antwerp document religious devotions which were intensely corporeal. Biographical sketches of individual sisters describe spiritual practices in which prayer and meditation, often enhanced by visual or bodily contact with devotional objects, fostered mystical encounters with Christ, saints, and martyrs. The Passion and the physical torment of holy figures who died for their faith infused the cloister's spirituality. At Antwerp, nuns encountered stories of suffering in devotional books and in hagiographical accounts of both the early Christian, and the more recent English, martyrs. They might also engage physically with Christ and saints through the cloister's relic collection and other objects of devotion. This article explores the religious milieu at Antwerp, considering the nuns' spiritual proclivity for suffering, which was inspired in part by their religious exile from England. It argues that a culture of martyrdom infused private devotional practices and shaped the convent's corporate identity.